2016
DOI: 10.1128/aac.02888-15
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of the Pharmacokinetics of Cefotaxime in Critically Ill Patients with Acute Kidney Injury Treated with Continuous Renal Replacement Therapy

Abstract: h The objective of this study was to describe the pharmacokinetics of cefotaxime (CTX) in critically ill patients with acute kidney injury (AKI) when treated with continuous renal replacement therapy (CRRT) in the intensive care unit (ICU). This single-center prospective observational pilot study was performed among ICU-patients with AKI receiving >48 h concomitant CRRT and CTX. CTX was administered intravenously 1,000 mg (bolus) every 6 h for 4 days. CRRT was performed as continuous venovenous hemofiltration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…However, higher total V of 26–32 L has been reported for patients with liver disease in different disease stages [ 23 ]. Koedjik et al [ 24 ] showed a median total V in ICU patients on renal replacement therapy of 22.5 L, results that are in line with this current investigation. High V in ICU patients can be attributed to fluid leakage into the interstitial space and the use of resuscitation fluids [ 4 ], an effect that could be further pronounced by the high proportion of burn patients (35%) in this study.…”
Section: Discussionsupporting
confidence: 91%
“…However, higher total V of 26–32 L has been reported for patients with liver disease in different disease stages [ 23 ]. Koedjik et al [ 24 ] showed a median total V in ICU patients on renal replacement therapy of 22.5 L, results that are in line with this current investigation. High V in ICU patients can be attributed to fluid leakage into the interstitial space and the use of resuscitation fluids [ 4 ], an effect that could be further pronounced by the high proportion of burn patients (35%) in this study.…”
Section: Discussionsupporting
confidence: 91%
“…In children and neonates targets ranged from 75 to 100% 36 . In adults, targets of 100% of total or free concentration above or 4–5 times above the (actual measured) MIC have also been used in the critically ill 11,27,37,38 . In concordance with Aardema et al .…”
Section: Discussionmentioning
confidence: 95%
“…MIC have also been used in the critically ill. 11,27,37,38 In concordance with Aardema et al we used 100% fT> MIC ECOFF. The MIC ECOFF was used to account for variability in MIC testing and natural variability within isolates.…”
Section: Discussionmentioning
confidence: 97%
“…Cefotaxime is effectively used against various microbial strains responsible for skin, lower respiratory, urinary tract, intra-abdominal, bone and joint, and CNS infections [ 15 , 16 ]. Thus, it is considered to be an effective antifouling agent for nanoencapsulation with a high in vitro activity, favorable pharmacokinetics, and a moderate molecular weight [ 17 ].…”
Section: Introductionmentioning
confidence: 99%